Peningkatan Hasil Belajar Melalui Model Pembelajaran Problem Based Learning Materi Iman Kepada Malaikat Pada Peserta Didik Kelas 2 SDN 23 Painan Utara - Marsita, Afneli (EduSpirit : Jurnal Pendidikan Kolaboratif, 2025)
This study aims to investigate the impact of using interactive videos in the Problem Based Learning (PBL) model on students’ learning outcomes in the Islamic Religious Education (PAI) subject at SDN 23 Painan Utara. This research was conducted as a classroom action research (CAR) using the Kemmis and Taggart model, which consists of cycles of planning, action, observation, and reflection. The study was carried out in two cycles involving 10 second-grade students. The results showed an improvement in students’ learning outcomes after the implementation of the PBL model with interactive videos. In Cycle I, the average score of students was 68.5 with a class completeness of 60%, while in Cycle II, the average score increased to 86 with a class completeness of 93.33%. This study concludes that the use of interactive videos in PBL effectively enhances students’ learning outcomes.